A facile green synthesis of nanostructured Gold–Silver@Carbon (Au–Ag@C) nanocatalyst and its applications - Kavitha P; Shanthi C; Ramanujam Kannan (Kuwait Journal of Science)
In this communication, the room-temperature synthesis of gold–silver nanostructures using ascorbic acid (AA) by simple one-step process is reported. Furthermore, the core–shell-type of gold–silver@carbon catalyst (Au–Ag@C) has been derived by microwave irradiation. The surface morphology expresses the neat single metal and bimetal formation. The AA acts as a reductant as well as a stabilizer of metal nanoparticles (MNPs). The microscopic studies reveal the formation of MNPs as quantum dots (~3–5 nm). The excess reductant has been used as a precursor for carbon and in some case it forms as nanowires. The catalyst Au–Ag@C shows the excellent catalytic activity toward 4-nitrophenol reduction at room temperature. The proposed method is facile, fast and eco-friendly for the synthesis of Au–Ag MNPs.